Biomechanical evaluation of caudally and buccally screwed customised reconstruction plates for lateral segmental defects of mandible. Issue 8 (October 2021) - Demir, E.; Yalçın, G.; Kalaycı, A.; Sağlam, H.
Abstract: The aim of this study was to compare locking reconstruction plates with caudobuccally screwed custom mandibular reconstruction plates in bridging lateral mandibular segmental defects. The in vitro study was conducted on 13 polyurethane mandibles. A total of 7 mandibles with lateral segmental defects were bridged with locking reconstruction plates in group I, 6 mandibles with the same standard defect were bridged with caudobuccally screwed customised reconstruction plates in group II. Mean yield displacement, yield load, and displacement at 80 N (Newtons), 100 N, 200 N, 300 N loading were compared among the 2 groups. The mean (SD) displacement for Group I was 11.27 (3.6) mm, Group II was 21.08 (2.5) mm. Group II had signiﬁcantly greater (p=0.0001) displacement when compared with Group I. The mean (SD) force before failure for Group I was 638.4 N (127.2), Group II was 1398. 3 N (162.7). Group II withstood signiﬁcantly greater force than Group I (p=0.0001). The study reveals that the caudobuccally screwed custom reconstruction plates can significantly enhance yield load as preserving the preoperative shape of the face and mandible.